Quantum theory of phonon-assisted exciton formation and luminescence in semiconductor quantum wells - Meier, Torsten; Thränhardt, A.; Kuckenberg, S.; Knorr, A.; Koch, S.W. (Physical Review B)
The phonon scattering assisted luminescence of semiconductor quantum well excitons after short pulse excitation is investigated. The presented analysis is based on the low-density limit of a set of equations for quantum correlation functions for electrons, phonons, and photons. The dynamics of the correlation functions describes the optical excitation and the decay of the coherent exciton polarization as well as the generation of an incoherent exciton occupation and its luminescence decay. Numerical solutions of the equations of motion demonstrate strong competition effects of the exciton-phonon and the exciton-photon interaction on a picosecond time scale and lead to a nonmonotonous temperature dependence of the time-resolved spontaneous emission. The angle resolved emission resembles the generation and decay dynamics of the exciton density for different in-plane momenta.

Correlation-induced resonances in differential absorption of semiconductors - Meier, Torsten; Phillips, M.; Wang, H.; Koch, S.W. (Quantum Electronics and Laser Science Conference (QELS 2000))
Extensive recent studies have provided valuable understanding on the role of correlations between excitons in optical interactions in semiconductors.

Coulomb Memory Effects and Higher-Order Coulomb Correlations in the Excitonic Optical Stark Effect - Meier, Torsten; Brick, P.; Ell, C.; Hübner, M.; Prineas, J.P.; Khitrova, G.; Gibbs, H.M.; Sieh, C.; Jahnke, F.; Knorr, A.; Koch, S.W. (physica status solidi (a))
Differential absorption spectra of high quality InGaAs quantum wells were measured by means of pump–probe spectroscopy as a function of pump–probe delay, for different polarizations of the pulses, and different spectral detunings of the pump beam with respect to the 1s heavy-hole exciton. A clear redshift of the heavy-hole resonance is observed for large detunings and opposite circularly polarized pulses. Microscopic calculations that include not only the Hartree-Fock contribution but also higher-order Coulomb correlations reproduce the experimental findings very well. It is shown that the redshift is caused by Coulomb memory effects and is further enhanced due to the presence of the bound biexciton.

Comparison of the differential absorption obtained within a few-level model and the microscopic density-matrix theory - Meier, Torsten; Reichelt, Matthias; Sieh, C.; Koch, S.W. (physica status solidi (b))
A phenomenological multi-exciton level scheme is used to calculate the excitonic differential absorption as measured in pump and probe experiments. Numerical results are compared to those obtained by a fully microscopic density-matrix theory. For resonant excitation, optimized parameters yield qualitative agreement, but the phenomenological approach soon reaches its limit for non-resonant pumping.

Current Echoes induced by Coherent Control - Meier, Torsten; Stippler, J.; Schlichenmaier, C.; Knorr, A.; Lindberg, M.; Thomas, P.; Koch, S.W. (physica status solidi (b))
A scheme to generate an experimentally measurable current echo is proposed where current pulses are induced by a sequence of phase coherent optical pulses. Based on microscopic calculations for a one-dimensional tight-bindig model of a disordered two-band semiconductor it is predicted that excitation sequences can be taylored such that after two induced time-delayed current pulses a current echo pulse results.

Microscopic Theory of Optical Dephasing in Semiconductors - Meier, Torsten; Koch, S.W.; Jahnke, F.; Thomas, P. (Applied Physics A)
Dephasing, i.e. the decay of the optical interband polarization in a semiconductor results from destructive interference effects between different microscopic contributions. For a system without any disorder it is shown that the many-body Coulomb correlations lead to excitation-induced dephasing which becomes increasingly important at elevated excitation levels. The effect of disorder-induced dephasing is analyzed for low excitation levels, where the combined influence of excitonic, biexcitonic, and disorder scattering contributions lead to a temporal decay of the four-wave-mixing signal.

Ikonographie der Nazizeit - Adelmann, Ralf; Keilbach, Judith (Über Bilder sprechen. Positionen und Perspektiven der Medienwissenschaft)

"Halten Sie!" Ungeordnete Beobachtungen zu nationalsozialistischen Kriegsschauplätzen in digitalen Medien - Adelmann, Ralf; Keilbach, Judith (Frauen und Film)

"Man versucht sich zu öffnen". Video und RAF – eine abgeschlossene Geschichte - Adelmann, Ralf; Nohr, Rolf F. (Ästhetik & Kommunikation)

168 – kanal für fernsehtheorie. Fernsehwissenschaft: viele Gegenstände – eine Wissenschaft? Konzeption einer Einführung - Adelmann, Ralf (Über Bilder sprechen. Positionen und Perspektiven der Medienwissenschaft)

Verfahren des Authentischen. Überwachungskameras im Kontext des Fernsehens - Adelmann, Ralf (https://nachdemfilm.de/issues/no-2-show-reality-reality-shows)

Herausgefordert durch das Fremde – Aspekte einer Didaktik der Begegnung - Freitag, Christine (Katechetische Blätter 4/2000)

Medienerziehung in der Grundschule aus der Sicht von Schulleitungen. Ergebnisse einer schriftlichen Befragung mit ergänzenden mündlichen Interviews - Herzig, Bardo (Medienerziehung in der Grundschule. Grundlagen, empirische Befunde und Empfehlungen zur Situation in Schule und Lehrerbildung)

Informatik in den Sekundarstufen I und II unverzichtbar - Bartsch, P.; Becker, K.-H.; Hauf-Tulodziecki, A.; Herzig, Bardo; Lehmann, G.; Magenheim, J.; Schelhowe, H.; Siegel, C.; Wagner, W.-R. (Informatik Spektrum 23(2000)4)

Medienerziehung – eine neue Aufgabe für das Gymnasium - Herzig, Bardo (Mitteilungsblatt der Landeselternschaft der Gymnasien in Nordrhein-Westfalen e.V. 169)

Schlussbericht zum BIG-Modellvorhaben "Neue Medien und Lehramtsstudium". - Moll, S.; Tulodziecki, G.; Bender, P.

Non-linear mixed isotropic-kinematic hardening coupled with damage in the framework of finite deformation elasto-plasticity - Mahnken, Rolf; Del Linz, Sandra; Stein, Erwin

Geschichtsschreibung oder Roman? Zur Konstitutionslogik von Geschichtserzählungen zwischen Schiller und Ranke (1780–1824) - Süßmann, Johannes
Keywords: Schiller; Kleist; Ranke; Leopold von; Gatterer; Johann Christoph; Darstellungsfragen; Universalhistorie; Humboldt; Wilhelm von; Wieland; Christoph Martin

Adapting Optimization Techniques to Description Logics with Concrete Domains - Turhan, Anni-Yasmin; Haarslev, Volker (Proceedings of the 2000 International Workshop on Description Logics (DL2000), Aachen, Germany, August 17-19, 2000)

Representations of cones and conelike semigroups - Glöckner, Helge (Semigroup Forum)
Keywords: 43A35; 44A10; 43A65; 47B15